2020
DOI: 10.1111/jcmm.16204
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐angiogenesis role of FBXW7 in diabetic retinopathy by facilitating the ubiquitination degradation of c‐Myc to orchestrate the HDAC2

Abstract: Diabetic retinopathy (DR) is the most prevalently occurring microvascular complication in diabetic patients that triggers severe visual impairments. The anti‐angiogenesis role of FBXW7 has been identified in breast cancer. Therefore, this study intends to decipher the mechanism of FBXW7 in angiogenesis of DR. DR model was induced on mice using high‐glucose (HG) and high‐fat diet, and retinal microvascular endothelial cells (RMECs) isolated from normal mice were induced with HG, followed by evaluation of FBXW7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Our results revealed that FBXW7 might be a considerable factor in angiogenesis, DNA damage and cell senescence pathway, forming a complex regulatory network and playing an important role in ESCC. Corroborate with our ndings, Lihua Hu's study have shown that FBXW7 overexpression reduces angiogenesis in retinal tissues of mice with diabetic retinopathy [47]. Therefore, we applied the vascular mimicry experiments to determine the the effect of FBXW7 on angiogenesis of ESCC cells, and realized that FBXW7 could inhibited the angiogenesis ability of ESCC cells.…”
Section: Discussionmentioning
confidence: 64%
“…Our results revealed that FBXW7 might be a considerable factor in angiogenesis, DNA damage and cell senescence pathway, forming a complex regulatory network and playing an important role in ESCC. Corroborate with our ndings, Lihua Hu's study have shown that FBXW7 overexpression reduces angiogenesis in retinal tissues of mice with diabetic retinopathy [47]. Therefore, we applied the vascular mimicry experiments to determine the the effect of FBXW7 on angiogenesis of ESCC cells, and realized that FBXW7 could inhibited the angiogenesis ability of ESCC cells.…”
Section: Discussionmentioning
confidence: 64%
“…2 a, b, g, h, P < 0.05 or P < 0.01). The transcription factor c-Myc regulates the expression of several key genes related to angiogenesis [ 22 24 ]. Next, to find out whether c-Myc was involved in the increased expression of VEGF induced by WJ-MSCs ECM, we examined the effects of WJ-MSCs ECM on the expression of c-Myc.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with the conclusions from recent studies that HDAC acts as a regulator in tumor via changing the nucleosome conformation of tumor cells. It is well acknowledged that HADC participates in cellular modulation in various cells by regulating miRNAs, for example, HDAC2 regulates miR-503-5p in esophageal squamous cell carcinoma [ 35 ], HDAC2 promotes the endothelial dysfunction induced by diabetes [ 36 , 37 ], and HDACs regulate the cellular differentiation in neurodegenerative diseases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%